OPTIMALISASI PENERAPAN TRANSLANGUAGING BERBASIS LATAR BELAKANG PENDIDIKAN ORANG TUA DI SMA NEGERI CIBINONG BOGOR - Octa Pratama Putra; Yoseph Tajul Arifin (UIN Sumatera Utara Medan, 2022)
Internal and external factors from a person influence the ability to communicate in multilingualism. Some parents act as educators as well as companions. In the early stages of child development, they usually share by mixing languages such as Indonesian and English. This habit can shape the character of a child later in communication activities. This study aimed to determine the effect of parents' educational background on students' speaking ability (Translanguaging). The research method used is the survey method. Samples were taken from as many as 40 students with a simple random technique. Data collection was carried out by distributing questionnaires directly to the example. Data analysis used descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics to find simple and multiple correlation coefficients, followed by a significance test of the correlation coefficient with the T-test. The results showed that there was a positive effect of parental educational background on students' speaking ability (Translanguaging) with a simple correlation coefficient score of r = 0.68, which is significant with t count (5.78) > t table (2.42) at α = 0.01.